13(x-4)=3(2x-14)-3x

Simple and best practice solution for 13(x-4)=3(2x-14)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(x-4)=3(2x-14)-3x equation:



13(x-4)=3(2x-14)-3x
We move all terms to the left:
13(x-4)-(3(2x-14)-3x)=0
We multiply parentheses
13x-(3(2x-14)-3x)-52=0
We calculate terms in parentheses: -(3(2x-14)-3x), so:
3(2x-14)-3x
We add all the numbers together, and all the variables
-3x+3(2x-14)
We multiply parentheses
-3x+6x-42
We add all the numbers together, and all the variables
3x-42
Back to the equation:
-(3x-42)
We get rid of parentheses
13x-3x+42-52=0
We add all the numbers together, and all the variables
10x-10=0
We move all terms containing x to the left, all other terms to the right
10x=10
x=10/10
x=1

See similar equations:

| 7=-w8 | | `9-2x=x-6` | | -3(2m-6)=-6 | | (4x+10)=50+(x+5) | | 4(2x+2)-4x=48 | | 73.5=6s^2 | | 3.5n/7=1/7 | | (5x+6)=(3x+7) | | 4(1-8x)=29-7x | | 2x=27=2x-11 | | 32.00+9.25x+15.00=124.25 | | 2x-(-11)=12 | | 9(3a-7)=-2a-15-4a | | 6y–1=2(3–y) | | 7x-1+11x-29=180 | | 6x+155=445 | | -4(y+6)+y=9 | | 7+3(6x+3)=52 | | 14x+15=192 | | 6a^2+14-5a=0 | | 5(e+6=75 | | 8x4=23-11 | | 27=7(x)+6 | | 3(x–7)+4=28–2x | | a−37=2/7 | | 8x2+20x+12=0 | | a−3/7=2/7 | | 2(x-4)+3=13-4x | | x^2-5x+43=57 | | -4s+8s+2=125 | | p=31/6=-21/2 | | −1+a=-6 |

Equations solver categories